Risk Control Strategy for Mobile Crane through Active Safety Barrier Using PIR Sensor: A Literature Review - Robi Kurnia; Nur Rohman Rosyid (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Mobile crane operations carry high accident risk in the line of fire zone, where workers face falling objects, load swing, and operator blind spots; national data show heavy-equipment accidents remain a significant contributor to occupational accidents, while control still relies on passive barriers dependent on worker compliance. Objective: This review examines theories and concepts underlying an active safety-barrier risk-control strategy using Passive Infrared (PIR) sensors in the line of fire zone of mobile crane operations. Method: A narrative literature review across nine themes: Hierarchy of Controls, Swiss Cheese Model, human error and human factors, ISO 31000:2018 risk management, mobile crane safety, the line of fire concept, the Bowtie method, passive-active safety barrier concepts, and PIR sensor technology. Result and Discussion: The nine themes are complementary and can be integrated into one theoretical framework, positioning the PIR sensor as an engineering control that closes latent and active gaps in the Swiss Cheese Model, mitigates human-factor limitations, and can be evaluated through ISO 31000 risk matrices and Bowtie diagrams before and after implementation. Conclusion: A PIR-based active safety barrier integrated with systemic risk management is potentially more reliable than administrative controls and PPE alone in reducing line of fire accident risk